O „Attysie” Katullusa słów kilka: propozycja przekładu literackiego (A Few Words on Catullus’ Attis: A Literary Translation Proposal) - Wapniarski, Karol (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The article presents a new literary translation of Catullus’ Carmen LXIII (De Attide) into the Polish language. The text is accompanied by a short introduction outlining the mythic history of Attis and commenting on previous Polish translations.